AB1177 Aggressive sacroiliitis in a 4-year-old patient. Successful anti tnf treatment. (23rd January 2014) - Santa-Maria, V.; Iglesias, E.; Neth, O.; Camacho-Lovillo, M.
Abstract : Background: Enthesitis-related arthritis represents 3-11% of all patients with juvenile idiopathic arthritis (JIA). It affects more frequently males over 6 years old. This condition courses with arthritis that in the 90% of cases affects peripheral large joints (predominantly in lower extremities). Lumbosacral spine and enthesis can also be affected. Sacroiliac joints involvement is a rare condition at the beginning. It is often associated with HLA-B27. The diagnosis is made by exclusion according to the ILAR criteria and sometimes it is not easy. NSAIDs, corticosteroids, methotrexate and other DMARDs for treatment are used, but in patients with active sacroiliac arthritis initiation of a TNF inhibitor is recommended more readily Methods: We present the case of a 4½ -year-old boy who presented to us with a history of two years of intermittent proximal weakness of lower extremities and unstable gait. Results: The patient, with no significant past medical history, shows a waddling gait with a limp of two years of evolution, initiated after a mild trauma and chickenpox. He was given firstly a presumed diagnosis of transient hip synovitis with a normal X-ray. He maintains gait disturbance with intermittent pelvic girdle weakness (2-3/5) and right hip pain that improves with NSAIDs. He also complained of occasional right shoulder and bilateral heel pain. On examination he had unstable gait and a positive FABERE test. Neurologic exam was normal apart Gower's maneuver. The patient had no history of fever, rash or symptoms of diarrhea. Laboratory evaluation, included muscular enzymes, was normal. Normal PCR, maximum ESR 57mm/h. Serologies, autoimmunity workup (including ANA, ASLO, RF and celiac autoantibodies) and HLA-B27 were normal. The MRI revealed inflammatory lesions on the right sacroiliac joint that was worrisome for an inflammatory arthropathy but needed to rule out oncologic and infectious disease (image 1). Intravenous empiric antibiotics were started with no clinical response. Patient was started on oral corticosteroids and methotrexate treatment. After 4 months, in response to the slight improvement, anti-TNF was added reporting subsequently a significant clinical improvement. Corticosteroids and methotrexate have been suspended 4 months later. After 18 months in TNF blocking treatment he continues asymptomatic. Conclusions: Sacroiliacac disease is an unusual finding at initial presentation of Enthesitis-related arthritis, especially in young children, and sometimes it could mimic oncological disease, delaying the correct diagnosis. We present this case to illustrate that Enthesitis-related arthritis, could account for symptoms at an early age and not considering it could lead to multiple medical visits and diagnoses Early diagnosis and treatment are the basis to prevent significant effects on their quality of life. Anti-TNF agents are recommended for the treatment of enthesitis-related arthritis with axial involvement but nowadays there are no guidelines about when to withdrawn them and which percentage of patients would present disease relapse after that. Disclosure of Interest: None Declared